The unseen color aftereffect of an unseen stimulus: insight from blindsight into mechanisms of color afterimages. - Barbur, J; Weiskrantz, L; Harlow, J (1999)
We show here that, in the absence of a direct geniculostriate input in human subjects, causing loss of sight in the visual half-field contralateral to the damage, the pupil responds selectively to chromatic modulation toward the long-wavelength (red) region of the spectrum locus even when the stimulus is isoluminant for both rods and cones and entirely restricted to the subjects' "blind" hemifields. We also show that other colors are less or wholly ineffective. Nevertheless, red afterimages, generated by chromatic modulation toward the green region of the spectrum locus, also cause constrictions of the pupil even when green stimuli are themselves completely ineffective in the blind hemifield. Moreover, human subjects with damage to or loss of V1 are typically completely unaware of the stimulus that generates the aftereffect or of the aftereffect itself, both of which can be seen clearly in normal vision. The results show that pupillary responses can reveal the processing of color afterimages in the absence of primary visual cortex and in the absence of acknowledged awareness. This phenomenon is therefore a striking example of "blindsight" and makes possible the formulation of a model that predicts well the observed properties of color afterimages.